The Letters of Gediminas and the Problem of the First Dominican Church in Vilnius - Baronas, Darius (Vilnius University Open Series, 2024)
This article seeks to answer a seemingly simple question: did the Dominican church exist in Vilnius during the reign of the Lithuanian grand duke Gediminas (1316–1341)? It is mentioned in a several letters of this ruler that were produced in 1323 and, therefore, the idea that this church was a real thing received wide currency in numerous historiographical works. However, the comprehensible analysis of the contradictory information regarding this subject-matter, and the very absence of its mention in a letter addressed to the Dominicans themselves, allowed the author of this paper to advance a thesis that this church, in all probability and likelihood, did not exist at all. The fact that it was mentioned might be interpreted as an attempt by Gediminas to produce a most positive image of his (pagan) country in the eyes of the intended (Roman Christian) audience. In sum, Gediminas collaborated more closely with the Franciscans, but some Dominican friars also were present at his court in 1323. It would be extremely interesting to know whence they came. However, for the lack of conclusive evidence this question must remain unanswered.
Keywords: Gediminas; Letters of Gediminas; Dominicans; Franciscans; Vilnius